2019
DOI: 10.3389/fendo.2019.00273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin Supplementation on Hormonal, Inflammatory, Genetic, and Oxidative Stress Parameters in Women With Polycystic Ovary Syndrome

Abstract: Purpose: The aim of the current study was to evaluate the effect of melatonin administration on clinical, hormonal, inflammatory, and genetic parameters in women with polycystic ovarian syndrome (PCOS). Methods: The present randomized, double-blinded, placebo-controlled clinical trial was conducted among 56 patients with PCOS, aged 18–40 years old. Subjects were randomly allocated to take either 5 mg melatonin supplements ( n = 28) or placebo ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 52 publications
5
16
0
1
Order By: Relevance
“…One of the main findings of the present study was the beneficial effects of melatonin (alone or in combination) on testosterone. In line with our finding, Jamilian and colleagues indicated that melatonin administration for three months to PCOS women significantly reduced total testosterone [ 44 ]. In another study, long-term (6 months) melatonin administration to women with PCOS had beneficial effects on menstrual irregularities and biochemical hyperandrogenism [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…One of the main findings of the present study was the beneficial effects of melatonin (alone or in combination) on testosterone. In line with our finding, Jamilian and colleagues indicated that melatonin administration for three months to PCOS women significantly reduced total testosterone [ 44 ]. In another study, long-term (6 months) melatonin administration to women with PCOS had beneficial effects on menstrual irregularities and biochemical hyperandrogenism [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…A similar reduction of PCOS-related hirsutism and androgen levels after 12 weeks of melatonin supplementation was also found in a recent investigation by Jamilian et al (117). Thus, the therapeutic use of melatonin in women with PCOSrelated conditions shows promise, and should be explored further.…”
Section: Summary and Future Perspectivessupporting
confidence: 80%
“…In high concentrations (micromolar), melatonin is a free radical scavenger. At low levels (picomolar), melatonin acts by binding to membrane receptors [33][34][35].…”
Section: Discussionmentioning
confidence: 99%